Foodstuffs. Determination of aflatoxin B1, and the sum of aflatoxins B1, B2, G1 and G2 in cereals, shell-fruits and derived products. High performance liquid chromatographic method with post column derivatization and immunoaffinity column clean up. (15th November 1999) - British Standards Institution,
No abstract available